estudio de factibilidad para la apertura de una sucursal de la empresa comercial identidad (comercializadora y productora de camisas slim fit para hombres de 20-60 años) en la ciudad de Loja - Benítez Lozano, Gina Vanessa (2016)
The research was conducted with the purpose of conducting a "FEASIBILITY STUDY FOR OPENING A BRANCH OF THE COMMERCIAL COMPANY IDENTITY (DISTRIBUTOR PRODUCER AND SLIM FIT SHIRTS FOR MEN 20-60 YEARS) IN THE CITY OF LOJA" this business idea is to offer customers a broader product using the new point of sale; and likewise achieve encompass the local and regional future market; whose main objective was to develop an investment project to determine the feasibility of service and marketing of Slim-Fit shirts, in the city of Loja. For information and support the project, technical research methods used, and; The market study through a sample of 381 surveys 48813 men between the ages of 20-60 years, the city of Loja; procedure that allowed meet the potential demand, real demand and Effective Demand. It assessing the technical study based on the previous study, it is estimated to participate in the first year attending 7.09%; for the third year 6.73%; and in the fifth year 6.38%. In terms of administrative capacity, you will need a secretariat bookkeeper so you can carry details of the two local both principal branch. In the Financial Study, it allowed us to establish that the initial investment will be $ 17891.10, the total investment 34% equals $ 6,000 United States of America will be financed by credit BNF (National Bank of Development) to a term 10 years with semi-annual payments to 16% annual interest and the remaining 66% is equivalent to $ 11,891.10 will be invested by the parent company. Finally, the financial evaluation of the project was carried out based on the cash flows obtained for the five years of the project; basis on which the financial evaluation indicators were applied but before that the TMAR (Minimum Acceptance Cost Effective Rate) which is 20.40% for the mathematical calculation of the indicators was obtained, then the NPV was applied that was $ 40.126,54, favorable value determines that the project is financially feasible; IRR which is 101% higher than TMAR (20,40%) therefore higher performance is generated in the cost of debt was obtained; Benefit Cost Ratio is 0.22 cents, the PRC will be in eleven months and twenty-nine days. With respect to the indicator sensitivity analysis it was applied to two possible scenarios; the first is of increased costs with obtaining a 15.18% sensitivity coefficient of 0.9964, ie is less than one so the project is not sensitive to this economic scenario. The second is the decline in revenue with a 12.42% obtaining a sensitivity coefficient of 0.9940, ie it is less than one therefore the project is sensitive to this economic scenario. Last but not least with the information obtained, we proceed to perform the respective; conclusions and recommendations of this research